2018
DOI: 10.2174/0929867324666170404150351
|View full text |Cite
|
Sign up to set email alerts
|

New Drugs from Old Natural Compounds: Scarcely Investigated Sesquiterpenes as New Possible Therapeutic Agents

Abstract: Sesquiterpenes are natural products that have been extensively studied for their bioactivities, evidencing their potentiality as useful scaffolds for the development of drugs. Considering the different derivatives, the sesquiterpene lactones have been evaluated, especially on cancer cell and antineoplastic efficacy in in vivo studies. Their bioactivity is strictly related to the presence of the reactive α-methylene-γ-lactone group (αMγL). Nevertheless, several other sesquiterpenes lacking αMγL are known and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…These are few very important examples of the beneficial and useful properties of caryophyllene. We agree with Sut and co-workers' point-of-view that some of the considered old molecules, as sesquiterpenes, could possibly play an important role in drug discovery towards new discoveries [99].…”
Section: Beta (β)-And α-Caryophyllenesupporting
confidence: 91%
“…These are few very important examples of the beneficial and useful properties of caryophyllene. We agree with Sut and co-workers' point-of-view that some of the considered old molecules, as sesquiterpenes, could possibly play an important role in drug discovery towards new discoveries [99].…”
Section: Beta (β)-And α-Caryophyllenesupporting
confidence: 91%
“…Therefore, we predict that suppression of the lactate signaling pathway that induces M2-like macrophages should improve the macrophage phenotype to prevent cancer. Natural compounds are a major source of current chemotherapeutic agents, and the chemotherapeutic and chemopreventive effects of such compounds have been demonstrated both in preclinical and clinical studies [18]. Therefore, identification of candidate compounds with antitumor activity from the natural compound library has an important role in the research and development of new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Our present data demonstrated that suppression of the lactate signaling pathway that induces M2-like macrophages should change macrophage functions to prevent cancer proliferation, migration, and angiogenesis. It is believed that natural compounds are a good source of new drugs [18]. Withanolide D (C4b-C5b, C6b-epoxy-1-oxo-,20b, dihydroxy-20S, 22R-witha-2,24-dienolide; C28H38O6, MW 470.6; WithaD) is a steroidal lactone isolated from the leaves and roots of Withania Somnifera [19], which is one of the most reputed Indian medicinal plants and forms the essential constituent of more than 100 traditional medicine formulations [20].…”
Section: Withanolide D Decreased Cancer Growth and Angiogenesis By Atmentioning
confidence: 99%
“…There is a strong interest to plant compounds as potential pharmacological agents due to their effectivity, safety and a wide spectrum of biological activities, including anticancer effect (Amin et al 2009;Fulda 2010;Mondal et al 2012;Ouyang et al 2014). Terpenoids are quite promising as chemotherapeutic agents among potential anticancer drugs (Modzelewska et al 2005;Dall' Acqua et al 2011;Safi et al 2016;Suta et al 2017). One of such compounds is ferutinin, a sesquiterpene isolated from plants of Ferula genus (Umbelliferae family).…”
Section: Introductionmentioning
confidence: 99%